The role of the editor in postgraduate research: A survey of supervisors' perceptions - Kruger, Haidee; Bevan-Dye, Ayesha (South African Journal of Higher Education, 2016)
This article presents the empirical findings of a study undertaken to compare the views of editors and supervisors concerning the appropriate level of editorial intervention in the production of postgraduate dissertations and theses within the South African higher education context. Masters and doctoral students are required to demonstrate scholarship by presenting their research in a clear, well-structured manner that is in accordance with the rigors of academic writing. The lack of such writing and presentation skills is increasingly being recognised as a significant obstacle to the successful completion of postgraduate qualifications. Against the background of these and other problems, the traditional supervisory model, which emphasises monitoring the student’s autonomous research in a dyadic student-supervisor relationship, is shifting towards a collaborative mentoring model that comprises several role players, including a professional language editor. The involvement of an editor raises issues concerning the dimensions the editor should become involved in, the degree of editorial intervention and the method of editing. In order to gain a balanced perspective on these issues, a self-administered questionnaire comprising an inventory of editing tasks, modes of editing and modes of querying was e-mailed to a census of South African editors registered with the South African Translators’ Institute and/or the Professional Editors’ Group. The same questionnaire, with minor adjustments, was e-mailed to a census of supervisors’ employed at South African universities that had agreed to participate in the study. The findings indicate that while there was a convergence of editor-supervisor opinion concerning the structural and content editing tasks not being appropriate, opinions differ on the stylistic and copyediting tasks considered appropriate, with supervisors adopting a more conservative view. The combined responses yielded a restricted set of tasks limited to only the most basic copyediting tasks that are viewed as appropriate in the editing of dissertations and theses.